(untitled) (Revista da Universidade Federal de Minas Gerais, 2012)
The standard cosmological model suggests that after the “Big Bang”, 14 billion of years ago, the universe entered a period of expansion and cooling. In the first one millionth of a second appear quarks, glúons, electrons and neutrinos, followed by the appearance of protons and neutrons. In this paper, we describe the “cosmic battle” between gravitation and energy, responsible for the lighter chemical elements and the formation of the stars. We describe the thermodynamics of irreversible processes of systems which are far away from equilibrium, a route that is followed by the universe, seen as a living system.